Association between breast cancer risk and disease aggressiveness: Characterizing underlying gene expression patterns. Issue 4 (5th September 2020) - Ugalde‐Morales, Emilio; Grassmann, Felix; Humphreys, Keith; Li, Jingmei; Eriksson, Mikael; Tobin, Nicholas P.; Borg, Åke; Vallon‐Christersson, Johan; Hall, Per; Czene, Kamila
Abstract: The association between breast cancer risk defined by the Tyrer‐Cuzick score (TC) and disease prognosis is not well established. Here, we investigated the relationship between 5‐year TC and disease aggressiveness and then characterized underlying molecular processes. In a case‐only study (n = 2474), we studied the association of TC with molecular subtypes and tumor characteristics. In a subset of patients (n = 672), we correlated gene expression to TC and computed a low‐risk TC gene expression (TC‐Gx) profile, that is, a profile expected to be negatively associated with risk, which we used to test for association with disease aggressiveness. We performed enrichment analysis to pinpoint molecular processes likely to be altered in low‐risk tumors. A higher TC was found to be inversely associated with more aggressive surrogate molecular subtypes and tumor characteristics ( P  < .05) including Ki‐67 proliferation status ( P  < 5 × 10 −07 ). Our low‐risk TC‐Gx, based on the weighted sum of 37 expression values of genes strongly correlated with TC, was associated with basal‐like ( P  < 5 × 10 −13 ), HER2‐enriched subtype ( P  < 5 × 10 −07 ) and worse 10‐year breast cancer‐specific survival (log‐rank P  < 5 × 10 −04 ). Associations between low‐risk TC‐Gx and more aggressive molecular subtypes were replicated in an independent cohort from The Cancer Genome Atlas database (n = 975). Gene expression that correlated with low TC was enriched in proliferation and oncogenic signaling pathways (FDR < 0.05). Moreover, higher proliferation was a key factor explaining the association with worse survival. Women who developed breast cancer despite having a low risk were diagnosed with more aggressive tumors and had a worse prognosis, most likely driven by increased proliferation. Our findings imply the need to establish risk factors associated with more aggressive breast cancer subtypes. Abstract : What's new? The Tyrer‐Cuzick score for assessing breast cancer risk integrates information on lifestyle, reproductive, and familial factors, including BRCA mutation status. The relationship between Tyrer‐Cuzick score and specific breast cancer subtypes, however, remains unclear. In this investigation, five‐year, low‐risk Tyrer‐Cuzick gene expression profile, expected to be negatively correlated with risk, was associated with certain, more aggressive breast cancer subtypes, including basal‐like and HER2‐enriched subtypes. Analyses further indicate that genes and biological pathways involved in increased proliferation underlie this association. The findings draw attention to factors relevant to aggressive breast cancer subtypes that are not yet captured in risk assessment tools.